2020
DOI: 10.3390/ma13173811
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Kaolin-Supported g-C3N4/CeO2 Composites with Enhanced Photocatalytic Removal of Ciprofloxacin

Abstract: Herein, novel ternary kaolin/CeO2/g-C3N4 composite was prepared by sol-gel method followed by hydrothermal treatment. The self-assembled 3D “sandwich” structure consisting of kaolin, CeO2 and g-C3N4 nanosheets, was systematically characterized by appropriate techniques to assess its physicochemical properties. In the prerequisite of visible-light irradiation, the removal efficiency of ciprofloxacin (CIP) over the kaolin/CeO2/g-C3N4 composite was about 90% within 150 min, 2-folds higher than those of pristine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 56 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The 2D layers of conjugated sheet of tri-s-triazine specifies the interlayer stacking distance of 0.329 nm -0.333 nm, and corresponds to the (002) plane of 2θ = 26.6˚ denoted as C3N4 structure [42]. Apart from that, the amorphous structure of C3N4 was also observed which displayed as a corrugated structure [30]. It was suggested that the formation of amorphous structure responsible to the reduction of XRD peak intensity for (100) and (002) planes of C3N4.…”
Section: Transmission Electron Microscope (Tem) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D layers of conjugated sheet of tri-s-triazine specifies the interlayer stacking distance of 0.329 nm -0.333 nm, and corresponds to the (002) plane of 2θ = 26.6˚ denoted as C3N4 structure [42]. Apart from that, the amorphous structure of C3N4 was also observed which displayed as a corrugated structure [30]. It was suggested that the formation of amorphous structure responsible to the reduction of XRD peak intensity for (100) and (002) planes of C3N4.…”
Section: Transmission Electron Microscope (Tem) Analysismentioning
confidence: 99%
“…Doping cerium oxide (CeO2) with g-C3N4 was predicted to improve the limitations of the photocatalyst. CeO2 has gained popularity due their abundance, inexpensive, inert, non-toxic, high stability in absorption of photon energy, and excellent transfer of charged electron promoting electronhole separation which would enhance photocatalytic activity [30]- [33]. The g-C3N4/CeO2 composite would form a heterojunction structure supporting the separation for photogenerated electron-hole.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the photocatalyst can reduce O 2 to H 2 O 2, which then will react with the e À CB to form • OH (Jiang et al 2012;Wen et al 2017;Karbasi et al 2020). The positively charged holes of VB (h þ ) is more positive than the reduction potential of OH À / • OH (þ 2.38 eV) (Hou et al 2017;Huang et al 2020;de Melo Santos Moura et al 2021), which allows it to oxidize hydroxyl ions to form hydroxyl radicals. In addition, the h þ is a strong oxidizing agent that can directly degrade MB (Garcia-Segura & Brillas 2017).…”
Section: Proposed Photo Degradation Mechanismmentioning
confidence: 99%
“…2D-2D g-C 3 N 4 /K + Ca 2 Nb 3 O 10 -nanosheet heterojunctions were evaluated by Jiang et for photocatalytic degradation of TCH under visible light.The composite could degrade 81 % of TC in 90 min. [120] Huang et al [121] synthesized ternary kaolin/CeO 2/ g-C 3 N 4 composite by sol-gel method followed by hydrothermal reaction. The composite consisted of a self-assembled 3D sandwich-like structure comprising CeO 2 , kaolin, and g-C 3 N 4 nanosheets.…”
Section: Carbon-based Heterostructurementioning
confidence: 99%
“…Huang et al [121] . synthesized ternary kaolin/CeO 2/ g‐C 3 N 4 composite by sol‐gel method followed by hydrothermal reaction.…”
Section: Different Composites and Heterostructures In Antibiotic Removalmentioning
confidence: 99%